Genome-wide analysis of the C2H2-type zinc finger protein family in rice (Oryza sativa) and the role of OsC2H2.35 in cold stress response - Songguo Wu; Yuzhang Chen; Jianguo Li; Chunli Fu; Xiaoying Luo; Jingzhen Wang; Xincheng Wan; Ke Huang; Hailian Zhou; Guosheng Xie; Zhengdan Wu; Lingqiang Wang (Plant Stress)
Cold can be a tough challenge for rice cultivation, impacting its growth and overall productivity. The Cys2His2 (C2H2) zinc finger (ZF) genes are essential for plants’ responses to abiotic stress. In this study, we identified 99 OsC2H2 genes within the Oryza sativa japonica genome, detailing their gene structure, conserved C2H2-ZF domains, and motif compositions for the first time. We also examined the temporal expression patterns of these genes under cold, heat, drought, flooding, and salt stress. Interestingly, we found that OsC2H2.35 was upregulated during cold stress, and CRISPR/Cas9 editing of this gene enhances rice cold tolerance in seedlings. RNA-seq results showed that OsC2H2.35 negatively regulates several COR genes, including DEHYDRATION-RESPONSIVE ELEMENT BINDING FACTORS 1 s (OsDREB1A, OsDREB1B, and OsDREB1C). Specifically, OsC2H2.35 can directly bind to the promoters of OsDREB1A and OsDREB1C. Osc2h2.35 greatly enhances cold tolerance while preserving all essential agronomic traits, making it a valuable gene target for the genetic improvement of rice.